2013
DOI: 10.9790/2380-0230710
|View full text |Cite
|
Sign up to set email alerts
|

Mastitis incidence and bacterial causative agents isolated from lactating she-camel (Camelus dromedaries).

Abstract: This study was carried out to determine the incidence of mastitis in lactating she-camel in North Kordofan State, Sudan. Furthermore, the causative bacterial agents were identified. Sixty lactating she-camels were examined clinically for mastitis. Thereafter milk samples (n= 216 samples) were collected from each quarter of the udders of the she-camels. The samples were subjected to white side test (WST), somatic cell count test (SCC) and bacteriological examination. The results of the clinical examination reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 1 publication
4
17
0
Order By: Relevance
“…The present study showed that the good combination of sensitivity and specificity of these tests was obtained with a thresholds of 240000 cell/ml and score trace of CMT was considered as positive, respectively. This finding is supported by the report of Alamin et al (2013) who suggested that a threshold of SCC more than 2.5 × 105 cells/ml can be considered as indication of udder infection in camel. Sensitivity of CMT observed in our study was lower than that reported by Younan et al (2001) which revealed a rate ranging from 68 %-77 % for major pathogen (S. agalactiae and S. aureus) in camel and that observed by Sharma et al (2010) in cattle.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The present study showed that the good combination of sensitivity and specificity of these tests was obtained with a thresholds of 240000 cell/ml and score trace of CMT was considered as positive, respectively. This finding is supported by the report of Alamin et al (2013) who suggested that a threshold of SCC more than 2.5 × 105 cells/ml can be considered as indication of udder infection in camel. Sensitivity of CMT observed in our study was lower than that reported by Younan et al (2001) which revealed a rate ranging from 68 %-77 % for major pathogen (S. agalactiae and S. aureus) in camel and that observed by Sharma et al (2010) in cattle.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, previous reports have confirmed that milk SCC can be used as a screening test to detect subclinical mastitis in camels (Bekele and Molla, 2001;Saleh and Faye, 2011). However, Alamin et al (2013) reported that the SCC couldn't be used for detection of subclinical mastitis in camel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Camel mastitis has been estimated to affect more than 25% of lactating she-camel [7,8]. It is also known to cause approximately 70% losses in milk production [9].…”
Section: Introductionmentioning
confidence: 99%